THE EFFECT OF MIXED ANIMAL-VEGETABLE OILS IN FEED ON EARLY GONADAL MATURATION OF MALE ASIAN REDTAIL CATFISH (Hemibagrus nemurus) - Mujtahidah, Tholibah; Tartila, Shobrina Silmi Qori; Azril, Muhammad; Risqulloh, Sultan Jibran; Oktavian, Muhammad Abizar Sakti; Azmi, Rifky Tsabitul; Fatikasari, Amelia (Politeknik Kelautan dan Perikanan Jembrana, 2025)
Male broodstock candidates of Asian redtail catfish tend to have aggressive behaviour due to excessive testosterone production, which is exacerbated by poorly-regulated high-cholesterol feeding practices. This study aimed to suppress these conditions by administering the dietary combination of animal and plant-based oils during pre-gonadal maturation of male broodstock candidates (BW: 215.83±41.28 g; BL: 272.12±19.89 mm), reared in a 2 × 1 × 1 m3 net cage with the stocking density of two fish per cage. This study was conducted using a completely randomized design with three dietary combination treatments (2% of each oil dosage) with four replicates: base feed with no mixed dietary oil (K), mixed fish oil-maggot oil (IM), and mixed fish oil-palm oil (IS). All parameters, namely reproductive performance (final length/Pt, final weight/Wt, feed intake/FI, gonadosomatic index/GSI, and hepatosomatic index/HSI) and blood chemistry profile (total cholesterol/TC, high-density lipoprotein/HDL, triglycerides/TG, and glucose/GLU), were statistically tested their significance using the analysis of variance and Duncan’s multiple range test with 95% confidence level. Significant differences were found in Pt and Wt (p<0.05), where the dietary combination of oils (IM-IS) showed higher Pt and Wt values than the dietary without the mixed oils (K). The IM treatment obtained the highest TG level (159.98±38.44 mg dL-1; p<0.05), yet showed no significant differences from the other treatments in TC, HDL, and GLU levels (p>0.05). This study concludes that the dietary combination of fish oil (2%)-maggot oil (2%) improves lipid deposition during pre-gonadal maturation and regulates energy storage through weight gain, without jeopardizing the somatic growth (length) of male Asian redtail catfish broodstock candidates.Calon induk ikan baung jantan memiliki sifat agresif yang salah satunya disebabkan produksi testosteron berlebih akibat pemberian pakan dengan kadar tinggi kolesterol. Penelitian ini ditujukan untuk mengurangi dampak tersebut melalui evaluasi kombinasi minyak hewani dan nabati pada pakan selama fase awal kematangan gonad calon induk ikan baung jantan (BW: 215,83±41,28 g; BL: 272,12±19,89 mm), yang dipelihara pada hapa ukuran 2 × 1 × 1 m3 dan padat tebar sebesar dua ekor ikan per hapa. Penelitian ini menggunakan rancangan acak lengkap dengan tiga perlakuan pakan kombinasi (dosis tiap minyak 2%) dan empat ulangan, yaitu pakan tanpa kombinasi (K), pakan dengan kombinasi minyak ikan-maggot (IM), dan minyak ikan-sawit (IS). Seluruh parameter, yaitu kinerja reproduksi (panjang akhir/Pt, bobot akhir/Wt, total konsumsi pakan/FI, indeks somatik gonad /GSI, dan indeks somatik hati /HSI) dan profil kimia darah (total kolesterol/TC, high-density lipoprotein/HDL, trigliserida/TG, dan glukosa/GLU), dianalisis menggunakan analisis sidik ragam dan uji jarak berganda Duncan dengan derajat kepercayaan 95%. Perbedaan nyata ditunjukkan pada Pt dan Wt (p<0,05), dimana kombinasi minyak IM-IS menunjukkan nilai Pt dan Wt yang lebih tinggi dibandingkan tanpa pemberian kombinasi minyak (K). Perlakuan IM memperoleh konsentrasi TG tertinggi (159,98±38,44 mg dL-1; p<0,05), namun menunjukkan tidak adanya perbedaan nyata terhadap perlakuan lainnya pada konsentrasi TC, HDL, dan GLU. Penelitian ini menyimpulkan, bahwa kombinasi minyak ikan (2%) dan minyak maggot (2%) mampu memperbaiki penyimpanan lemak untuk fase awal kematangan gonad (trigliserida dalam serum darah) dan mendorong penyimpanan energi melalui peningkatan bobot, tanpa mengganggu pertumbuhan somatik (panjang) dari calon induk ikan baung jantan.